Comparison of Cognitive Function of Ischemic Stroke Patients with and without Pneumonia - Amanda Diannisa Azzahra; Lisda Amalia; Chandra Calista; Sofiati Dian; Siti Aminah; Paulus Anam Ong (Faculty of Medicine Universitas Padjadjaran, 2021)
Background: Pneumonia is a common complication of ischemic stroke that may worsens brain injury, leading to cognitive impairment as well as patient outcome. The aim of this study was to compare cognitive function in ischemic stroke patients with and without pneumonia.Methods: This study was a comparative numerical analytic retrospective cross-sectional study that was conducted from September 2020 to February 2021. This study used data from ischemic stroke patients treated at Dr. Hasan Sadikin General Hospital in 2019 with the total sampling method. Data were stratified into patients with pneumonia and without pneumonia. The mini mental state examination (MMSE) was used to measure cognitive function in both groups and scores were compared using the Mann-Whitney Test.Result: Of the 164 data, 25 were patients with pneumonia and 139 without pneumonia. Male patients were predominantly prevalent in the pneumonia and non-pneumonia groups. Hemiparesis was the most common neurological deficit. The MMSE score was significantly lower in the pneumonia group (22.6 ± 5.4 vs. 24.7 ± 4.8, respectively; p-value=0.032). Conclusion: Cognitive function is more prevalent in ischemic stroke patient with pneumonia compared to non-pneumonia. However, other factors such as recurrent stroke and possible vascular risk factors should be considered for future studies to better identify the relationship between ischemic stroke and pneumonia.